Concurrent Osteosarcoma Theranostic Strategy Using Contrast-Enhanced Ultrasound and Drug-Loaded Bubbles - Tai-Tzung Kuo; Chung-Hsin Wang; Jir-You Wang; Hong-Jen Chiou; Ching-Hsiang Fan; Chih-Kuang Yeh (MDPI AG, 2019)
Osteosarcoma (OS) is the most common bone tumor in children and teenagers. The multidrug resistant property of OS produces a major obstacle to chemotherapy, since the effective drug dose cannot be achieved via conventional drug delivery routes without serious systemic cytotoxicity. Microbubbles in conjunction with ultrasound (US) has recently been shown to spatially and temporally permeabilize the cellular membrane, promoting drug penetration into tumors. Here, we investigated whether drug (doxorubicin, DOX)-loaded bubbles (DOX-bubbles) can serve as drug-loaded carriers in combination with US in order to facilitate tumor drug delivery. The proposed bubbles have a high payload capacity (efficiency of 69.4 ± 9.1%, payload of 1.4 mg/mL) for DOX. In vitro data revealed that when used in combination with US (1-MHz), these DOX-bubbles facilitate DOX entering into tumor cells. In tumor-bearing animals, DOX-bubbles + US could provide 3.7-fold suppression of tumor growth compared with the group without insonation (1.8 ± 0.9 cm3 vs. 8.5 ± 2.2 cm3) because of the acceleration of DOX-induced tumor necrosis. In the meantime, the tumor perfusion and volume can be monitored by DOX-bubbles with contrast-enhanced ultrasound imaging. Our data provide useful information in support of translating the use of theranostic US-responsive bubbles for regulated tumor drug delivery into clinical use.